Workplace Learning for Critical Core Skills Development: Empirical Evidence From Singapore - Bi, Xiao Fang; Boo, Lena (International Journal for Research in Vocational Education and Training, 2025)
Context: Soft skills or critical core skills (CCS), e.g., communication, problem solving, etc, have been recognized by both individuals and organizations as important but at shortage in the labour market. Within this context, the development of CCS for the employees becomes more and more pressing for the organizations in order to cope with the everchanging demand of workforce. By clustering 2000 participants into seven occupation groups in terms of their similar patterns in the use of CCS, this article aims to show how workplace learning initiated by individuals in different occupations can forge a highly similar learning pathway to develop CCS for the purpose of their personal and professional development. Methods: Drawing on the quantitative results of 2000 participants from Singaporean workforce into seven occupational groups, a qualitative study using semi-structured interview questions that seek to understand how workplace learning attributes to the development of critical core skills. 39 participants were selected to represent the critical core skills profile of the seven occupation groups in Singapore. Unlike earlier research focusing on specific occupation, the present study provides cross-national evidence for the development of critical core skills. Findings: Participants' narratives of their workplace activities are analysed. The empirical study revealed that everyday practices at workplaces facilitate learning pathway more effectively than formal and structured training, for instance, learning from the experience, errors, and also peers within the community of practice. Conclusions: This paper provides an in-depth qualitative study of workplace activities across the diverse occupational groups in Singapore which is lacking in existing literature, including participation and involvement practices using the lens of situated learning theory to account for the development of critical core skills. As a result, this paper enriches the scarce research base about critical core skills development and participatory practices in the community of practices and its links to organisation-wide performance.